Insight to a tobacco user's mouth: An epidemiological study in Bhopal - Preeti P. Nair; Rhiti Chatterjee; Annette Bhambhal; Kavita Agarwal; Pooja Khare; Shiba Neelkantan (Journal of Oral Biology and Craniofacial Research)
Background: The rampant tobacco abuse is escalating the Indian health sector towards a future overburdened with high prevalence of cancer and potentially malignant conditions. Thus manifestations of tobacco abuse have become a widely recognized but poorly tackled public health issue. To understand the same, a study was conducted in a dental college of Bhopal, India. Methodology: A hospital based cross sectional study was done over a period of 1.5 years. Patients giving history of deleterious habits were included in the study. The form of tobacco/areca nut used, duration and frequency of usage and awareness regarding their ill-effects were recorded. All documented data was subjected to statistical analysis using chi-square test. Results: Out of 2033 individuals studied 21% were below the age of 25 years, 53% in 26–50 years, 20% in 51–75 years and 6% above 76 years of age with 85% being males. 67% used smokeless form, 21% smoked and 12% used tobacco in both smokeless and smoking form. 58% of the individuals had tobacco associated lesions, of which oral submucous fibrosis (OSMF) was the most prevalent. The relation between duration and frequency of abuse and occurrence of lesion was found to be statistically significant (p < 0.05). Conclusion: The smokeless form was most widely abused in this part of the country especially the younger population. OSMF, a premalignant condition with debilitating effects on the lifestyle, was the most prevalent lesion associated with tobacco use. These findings call for early and aggressive intervention methods be put into action.